Cross-examination of witness in criminal proceedings - Đurđević, Tijana (Glasnik Advokatske komore Vojvodine, 2019)
This paper analyses the cross-examination of witness in criminal proceedings, mentioned firstly in The Constitutional Act (2006) and finally introduced into our legal system by The Code of Criminal Procedure (2011). This concept implies the right of a party in criminal proceedings to examine a witness proposed by the other party. As this phase of examination is typical for adversarial model of criminal proceedings, the paper explains the basics of witness testimony in adversarial, but also in the mixed type of criminal proceedings, after which the characteristics of the criminal proceedings in our country are explained, having in mind the current Code of Criminal Procedure. In order to perceive the problem completely, the paper deals with the concept of witness in criminal proceedings as well as the cross-examination of the witness, through the most important domestic and international legal sources. Lastly, the goals and types of cross-examination of witness are explained and practical advices for examiners are given.